Prospects for innovative development of entrepreneurship in the regions - Tursunov Egamberdievich, Imomnazar; Naminova Antonovna, Kermen (THE INNOVATION ECONOMY, 2024)
One of the priority areas of the economic reform currently underway in Russia and Uzbekistan is the establishment and development of small and medium-sized businesses. The article describes the role, essence and significance of the digital and innovative economy in increasing the competitiveness of private entrepreneurship, small and medium-sized businesses. Also, proposals were put forward for their development in connection with the integration of science and higher education and internal and external factors of technological development. The article shows a new set of economic processes in a modern market economy, factors and risks of managing the transition to network mechanisms for innovative development of the economy. The economy of risks is the economy of high-tech and knowledgeintensive industries, characterized by the highest degree of political, economic, technological, financial and environmental uncertainties and risks. The article studies the development of small and medium-sized businesses in the context of new challenges and the formation of a digital economy in the regional space. The relationship and mutual influence of the development of SMEs and the regional economy is revealed. The necessity and importance of monitoring the development of small and medium-sized businesses in the region is substantiated